Utilization of the Aku Pintar Application as an Information Service Media in Determining Major Choices for Students of Al-Fityah IT High School, Pekanbaru - Yurika Ajeng, Tince; Rodin, Rhoni (SYNAPSI: Journal of Information Systems and Informatics Education, 2026)
Purpose of the study: This study aims to analyze the implementation of information services through the Aku Pintar application in assisting students of SMA IT Al-Fityah Pekanbaru in determining appropriate major choices based on their interests, talents, and academic potential through digital-based guidance and counseling services.Methodology This study employed a qualitative case study approach at SMA IT Al-Fityah Pekanbaru. Data were collected through semi-structured interviews, observations, and documentation. The participants consisted of one counseling teacher and five students. The study utilized the Aku Pintar application, smartphone devices, thematic analysis techniques, triangulation methods, and Holland’s career theory as the analytical framework.Main Findings: The findings revealed that the Aku Pintar application positively supported students in understanding their interests, talents, and educational pathways. The application improved students’ confidence in determining majors through aptitude and interest assessments, interactive information services, and counseling guidance. Accessibility through smartphones, counseling teachers’ support, student motivation, and parental involvement significantly contributed to the successful implementation of digital-based information services.Novelty/Originality of this study: This study offers a qualitative exploration of the implementation of information services through the Aku Pintar application within an Islamic integrated school context. The research integrates Holland’s career theory with digital counseling services and highlights students’ experiences, counseling teachers’ roles, and supporting factors in developing interactive and personalized educational technology-based guidance services.